Probabilistic seismic hazard assessment in complex fault systems: exploring the Longitudinal Valley of Taiwan - Ting-Ying Lu; Chung-Han Chan (Geoscience Letters)
Abstract This study validates several seismic models used in PSHA studies and evaluates their impact on hazard levels in the Longitudinal Valley, Taiwan, a region with high seismic activity and data quality. The Gutenberg–Richter (G-R) law, fitting well for small to moderate magnitudes, faces uncertainties at larger magnitudes due to limited data. The pure characteristic earthquake (PCE) model assesses maximum earthquake recurrence rates for each seismogenic structure, challenging due to longer recurrence intervals. The Seismic Hazard and Earthquake Rates in Fault Systems (SHERIFS) model, incorporating the G-R law and structure parameters, forecasts seismic activity for the study region and each individual seismogenic structure. The hazard maps, assessed based on two models, reveal differences, especially around the Milun Fault and southern tip of the Longitudinal Valley. The hazard curves for cities reflect varying hazard levels influenced by nearby faults. Based on the SHERIFS model, the hazard is distributed across various faults. This indicates that the SHERIFS model effectively allocates the occurrence rates for each magnitude. This underscores the importance of multiple seismic models for precise hazard assessment, which is crucial for understanding earthquake physics and future PSHA in Taiwan.